Dinamika Post-Traumatic Growth Pada Penyintas Intrauterine Fetal Death (IUFD) - Riska Samrohtul Maqmudah; Retno Pangestuti (Psychopolytan : Jurnal Psikologi, 2026)
Fetal death in the womb at >20 weeks of gestation is called Intrauterine Fetal Death (IUFD). Although traumatic events have a negative impact on an individual's psychology, such experiences also have the potential to bring about positive growth, known as post-traumatic growth. This study aims to explore the process of post-traumatic growth in Muslim female psychologists who are survivors of IUFD using a qualitative single case study approach. The research subjects are a Muslim female psychologist who survived IUFD and her significant other. Data collection was conducted through interviews, observations, and document analysis. Data were analyzed thematically through verbatim transcripts, repeated readings, coding with ATLAS.ti 25, grouping into sub-themes, and drawing patterns of post-traumatic growth, then presented in a narrative-descriptive manner. The results of the study show that subjects who lost their fetuses at 28 weeks of pregnancy felt deep sadness, shock, and denial of reality. The subjects then entered a turning point phase with social, spiritual, and psychological support. This process facilitated post-traumatic growth, which was characterized by more meaningful relationships with family, life orientation, strengthened spirituality, and greater empathy in their professional roles as psychologists. These findings imply the importance of social, spiritual, and mental health education support in post-trauma counseling.